2010
DOI: 10.1590/s0103-90162010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus loss by surface runoff in no-till system under mineral and organic fertilization

Abstract: The no-till system has been intensively used in the state of Paraná, Brazil, and it has increased the nutrients level at the soil surface. This has contributed for nutrient losses via runoff and consequently, offsite water pollution. The objective of this study was to evaluate phosphorus loss in surface runoff by simulated rainfall on an Oxisol, under no-till system following application of mineral fertilizer and liquid swine manure. Nitrogen, soil and water losses from the same study are reported in a separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 41 publications
1
13
0
5
Order By: Relevance
“…It should be noted, however, that longterm P applications and no-tillage tend to increase P concentrations on soil surface (Kleinman et al, 2009;Verbree et al, 2010), increasing potential risks of P losses, even in highly weathered soils (Barbosa et al, 2009;Bertol et al, 2010;Guardini et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that longterm P applications and no-tillage tend to increase P concentrations on soil surface (Kleinman et al, 2009;Verbree et al, 2010), increasing potential risks of P losses, even in highly weathered soils (Barbosa et al, 2009;Bertol et al, 2010;Guardini et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according MAGGI et al (2011), the result is also found linked to the fact that K + is a movable element in soil and is subjected to leaching. BERTOL et al (2010) reinforces this idea, stating that K + has low reactivity with soil which may cause an increased mobility. Previously, KING et al (1985) 2.58 - § Means followed by the same low case letter in the column do not differ by Tukey test at 5% significance for SWW and means followed by the same capital letter in the column do not differ by Tukey test at 5% significance for MF.…”
Section: Leachate Variablesmentioning
confidence: 60%
“…The surface-applied PS may be carried by runoff to watercourses, increasing P sol (Sharpley et al, 2003;Bertol et al, 2010;Gebler et al, 2012). The highest P sol concentrations were observed in W1 and the lowest in W4, which are the watersheds with the largest and smallest swine populations, respectively.…”
Section: Resultsmentioning
confidence: 99%